Storage and Thawing Practices of Expressed Breast Milk and Their Association with Growth in Infants Aged 0–6 Months - Nurbaiti; Herlina (Journal of Applied Holistic Nursing Science, 2026)
Background: Expressed breast milk (EBM) is one of the most commonly used alternatives for breastfeeding among working mothers to ensure that infants continue to receive adequate nutrition. The quality of expressed breast milk is highly influenced by proper storage and thawing practices. Inappropriate handling during these processes may reduce nutritional content and increase the risk of contamination, potentially affecting infant growth. Methods: This study employed a quantitative cross-sectional design using a total sampling technique involving 391 respondents. Data were analyzed using univariate and bivariate analyses. The Chi-square test was applied to examine the relationships between EBM storage practices, EBM thawing practices, and infant growth. Results: Statistical analysis revealed a significant association between expressed breast milk storage practices and infant growth (p < 0.001). A significant association was also found between expressed breast milk thawing practices and infant growth (p < 0.001). Conclusion: Proper storage and thawing practices of expressed breast milk play an important role in supporting the growth of infants aged 0–6 months.